Brayton technology for Concentrated Solar Power plants: Comparative analysis of central tower plants and parabolic dish farms. (1st November 2022) - García-Ferrero, J.; Merchán, R.P.; Santos, M.J.; Medina, A.; Calvo Hernández, A.
Abstract: Concentrated solar power plants intend to be key in the pool of renewable energy production technologies in the next future because of their versatility and high efficiency. In this work a comparative study between two promising technologies is developed. A central tower receiver surrounded by a heliostat field and a farm of parabolic dishes, both coupled to a hybrid Brayton cycle, are considered. Two power scales are surveyed (between 5 and 20 MW) at three different locations with quite different latitudes (between Sahara desert and medium European latitudes) and meteorological conditions. A modelling scheme developed by our group that allows to obtain the expected thermodynamic and thermo-economic plant records is applied. Key indicators like efficiency, net generated energy, levelized cost of electricity, and specific plant investment are calculated and analysed. Variability of natural gas prices and also land cost uncertainty are reflected on levelized cost of electricity range. Among the plants compared, minimum values are found within the interval [135–163] USD/MWh for central towers at the highest power considered and southern latitudes. In addition, the area needed for the installation of the plants and the influence of CO 2 taxes is also analysed. Displayed cashflows show larger investment costs for central tower than for dish farms. Finally, those systems are put into the context of other concentrated solar power, other renewable, like wind or photovoltaic, and other conventional power plants. Highlights: High temperature Brayton gas turbines are coupled to a central tower or dish farm. An in-house model is applied in order to obtain realistic thermo-economic predictions. Three locations with different meteorological conditions and latitudes are explored. Systems scalability is surveyed by simulating 5 MW and 20 MW plants. LCoE intervals considering gas and land prices, and also CO2 taxes are calculated.